Professional Dental Education in the Modern Russian Federation: Current Status and Prospects - Anzor Khaniev; Zhukova Nikolaevna; Ardavova Anatolievna (Strides in Development of Medical Education)
Background: In the Russian Federation, dentistry has become a very popular career choice among applicants, leading to a significant increase in the number of graduates from dental faculties and universities, as well as a growth in the number of educational institutions providing higher medical education in dentistry.Objectives: The aim of this study was to review the current status, requirements, and prospects of dental education in the Russian Federation.Methods: Statistical, informative, and analytical official reports in Russia, as well as foreign information sources, cross-sectional studies, and the data on official websites of higher education institutions were analyzed.Results: In the Russian Federation, there has been an increase in the number of dental universities and faculties, as well as the number of dentistry students over the past 10 years. There is a surge in the number of admitted students, the number of dentists graduating from universities, and clinical residents of dental specialties. At the same time, the tuition fees are the highest for all specialties and are going up every year. There is also an increase in the total number of dentists, and they are concentrated in Moscow and other big cities in the country.Conclusion: Currently, in the Russian Federation, we can speak of the skewness of medical education toward dentistry. To meet the challenges facing dentistry, it seems reasonable to match the future dental workforce with the future needs of the population. The current situation in the healthcare system of the Russian Federation needs to be improved for medical dentistry education and dental health staffing, and all these issues can only be solved by introducing fundamental changes.